RANCANG BANGUN PENGAMANAN AKSES MASUK PERKANTORAN BERBASISKAN PIN DAN RFID - Reza Restu Pratama; Irmayani Irmayani (INSTITUT SAINS DAN TEKNOLOGI NASIONAL, 2017)
ABSTRACTThe security system is so needed to protect the important assets and Data which are belong toa company. The high traffic of goods and people create a worry of assets and Data. Minimal securitysystem will make them easily stolen. Additional security system such as utilization technology of PINand RFID could minimize the crime of those assets. The implementation of security systems is on thedoor for employee’s entrance access. This system is applied into a control system usingmicrocontroller equipped with keypad interface and LCD. The integrated software with supportingequipment that allows the system to operates automatically. Employee’s security system beforeentering the room, will be read by microcontroller. The data will be processed to determine the workof the system and the instructions will be displayed on LCD. The keypad as a tool for pin setting.Entrance access security system based on PIN work by using radio frequency to read the informationfrom a small device called tag or transponder (transmitter + responder). Tag RFID will recognizeitself when it detects signals from a compatible device, that is RFID reader. So that the identificationprocess more flexible and easy to use. The control of microcontroller which is ATMega 8535,produce system of open-close door automatically.